2019
DOI: 10.3390/su11133587
|View full text |Cite
|
Sign up to set email alerts
|

The Organizational Culture of a Major Social Work Institution in Romania: A Sociological Analysis

Abstract: This study aims to document the specific organizational culture existing in the General Directorate for Social Work and Child Protection (DGASPC) in the Gorj county, Romania. This is a major social work institution in Romania, but one which (like most other social work institutions in this country) have rarely been subject to the type of sociological research as the one reported in this article. The present analysis can help leaders in this organization and other similar organizations to assess and improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
11
0
3
Order By: Relevance
“…Therefore, focusing on performance is crucial in an effort to survive. In this context, the corporate culture represents a major element of business management, which is supported by existing studies (Ogbonna and Harris 2000;Škerlavaj et al 2011;Rezaei et al 2016;Mullakhmetov et al 2019;Vlaicu et al 2019) and has a significant impact on their performance. An overview of actual literature associated with the corporate culture is given in this paper.…”
Section: Introductionmentioning
confidence: 76%
“…Therefore, focusing on performance is crucial in an effort to survive. In this context, the corporate culture represents a major element of business management, which is supported by existing studies (Ogbonna and Harris 2000;Škerlavaj et al 2011;Rezaei et al 2016;Mullakhmetov et al 2019;Vlaicu et al 2019) and has a significant impact on their performance. An overview of actual literature associated with the corporate culture is given in this paper.…”
Section: Introductionmentioning
confidence: 76%
“…A literature review revealed that interest in the present subject matter has mainly been related to disability in the workplace, with an emphasis on mainstreaming, discrimination, or how to accommodate adult PWDs in the workplace, as well as the impact of social grants for adult PWDs on recipients. The following are the main findings from the international literature by Maestas et al [19], Loyalka et al [20] and Wind et al [21], as well as those studies on the CRPD by Murungi [18], Ladner [22], Walker [23], Vlaicu et al [24] and Xu and Chen [25].…”
Section: Literature Reviewmentioning
confidence: 68%
“…• Esta obra está bajo una licencia de Creative Commons Atribución-CompartirIgual 4.0 Internacional (CC BY-SA 4.0) https://creativecommons.org/licenses/by-sa/4.0/deed.es https://www.produccioncientificaluz.org/index.php/rvg Twitter: @rvgluz _______________Revista Venezolana de Gerencia, Año 27 No. 97, 2022 contextos organizacionales logrando resultados valiosos tanto en el ámbito académico como profesional (Vlaicu, 2019).…”
Section: Instrumento De Evaluación De La Cultura Organizacional (Ocai...unclassified
“…Los estudios realizados en instituciones del área de la salud (Heritage, et al 2014;Van Huy et al 2020) Hay un número significativo de estudios realizados en otros sectores industriales, entre los que se encuentran electricidad, sector financiero, construcción, sector forestal, logística, hotelería, telecomunicaciones y servicios sociales. A pesar de la diversidad de contextos organizacionales, se pueden apreciar notables similitudes en los resultados de la mayoría de estos estudios, marcado por una cultura actual predominante de tipo Jerarquizada (Dela-Garza-Carranza et al, 2010;Kargas y Varoutas, 2015;Ližbetinová et al 2016;Soares et al 2018;Vlaicu et al 2019), y una cultura deseada de tipo Clan (Ližbetinová et al, 2016;Lorincová et al, 2020;Teräväinen et al, 2018).…”
Section: Tabla 3 Citas De Los Artículos Por Añounclassified